Unholy trinity : labor, capital, and land in the new economy - Foley, Duncan K. (Graz Schumpeter lectures, 2003)
Explores the relations between contemporary complex systems theory and Classical political economy, and applies the methods it develops to the problems of induced technical change and income distribution in capitalist economies.